Analisis Tren Penggunaan Aplikasi Kebugaran: Tinjauan Literatur Sistematis - Fidyah Salsabila Putri Sillehu; Arista Pratama; Asif Asif Faroqi (MDP Student Conference, 2026)
This study aims to analyze research trends related to the intention to use fitness applications through a Systematic Literature Review (SLR). The review was conducted by identifying, selecting, and evaluating relevant studies published between 2021 and 2025 using Google Scholar, Scopus, and SINTA databases. A total of 17 articles met the inclusion and quality assessment criteria. The results indicate that the UTAUT2 model is the most frequently used model in studies on fitness application usage intention. Several UTAUT2 variables, including Performance Expectancy, Hedonic Motivation, and Habit, are identified as the most dominant factors influencing usage intention. In addition, PLS-SEM is the most commonly applied data analysis method. This study is expected to serve as a reference in determining relevant models, variables, and research methods for future studies.